The Contribution of Foreign Affilliates to Productivity Growth Evidence from OECD Countries - Criscuolo, Chiara (OECD Science, Technology and Industry Working Papers, 2005)
This study uses new information to determine the role of foreign affiliates in productivity growth. The study has three aims. Firstly, the study quantifies the contribution of foreign affiliates to productivity growth in OECD countries using a growth accounting approach. Secondly, the analysis shows how much of this contribution derives from an increase in the employment share of foreign affiliates in the host country relative to an increase in the productivity of existing foreign affiliates. Thirdly, the study compares the presence of foreign affiliates across OECD countries. The information is derived by matching three OECD data sources: the STAN database for industrial analysis, the AFA (Activities of Foreign Affiliates) and FATS (Foreign Affiliates in Trade and Services) databases. Despite its limitations, this combined database provides longitudinal industry level information on both the presence and the productivity of foreign affiliates in OECD countries. The analysis confirms that foreign affiliates can make an important contribution to productivity growth. The contribution is larger in the manufacturing sector. In the services sector and in low-tech manufacturing sectors, the largest component of the contribution of foreign affiliates is due to the increased employment share of foreign affiliates. In medium- and high-tech sectors, the contribution is mainly driven by stronger productivity growth of existing foreign affiliates. In the United States the contribution is consistently driven by stronger productivity growth of existing foreign affiliates in both the manufacturing and the services sectors